Representasi Romantic Relationship dalam Film Wedding Agreement - Ahsani, Filardi Amal; Illahi, Azizun Kurnia (Tuturlogi: Journal of Southeast Asian Communication, 2022)
This research aims to analyze the portrayal of romantic relationships in the film "Wedding Agreement" involving arranged couples. The focus of the research is to explore how the representation of these relationships in the film relates to the social context of Indonesian society, as well as the relevance of the phenomena depicted in the film to the current conditions. The research method used is qualitative descriptive, with document analysis as the data collection technique. The use of discourse analysis with its two paradigms is chosen as the data analysis technique in this study because it can reveal culture and society in a discourse constructed through textual elements, namely the formalist and functionalist paradigms. The results show that the film "Wedding Agreement" represents several phenomena that occur in the social reality of Indonesia, such as arranged marriages, patriarchal culture, the influence of strong religious values, and high parental control over children. The question that arises is whether the phenomena portrayed in the film truly reflect the current state of society and to what extent the film can depict the actual issues faced by the community. Overall, "Wedding Agreement" provides a relevant representation of the social and cultural context of Indonesia.